O precedente vinculante segundo a constitucionalização do direito - Sampaio, Luana Ramos (2016)
This Master dissertation is a construction that aims to understand and situate the binding precedents (from diffuse control) brought from the new Civil Procedure Code, under constitutionalism parameters. The proposal is to analyze the binding precedent in a building that uses concepts of democratic constitutionalism (linked to state theory and philosophy of law) in a way that arrives in basic concepts of legal interpretation. When working a connection between the different doctrinaire currents work creates an integrative theory that clarify what would be the proposal of binding precedent in the NCPC and what the necessary adjustments to their establishment in national law. The method used to build the thesis was creating a logical-deductive reasoning from extensive and complex literature. The thesis is that the binding precedent is a natural effect of the constitutionalization of law and will only generate all the effects expected of it when constitutionalization process goes throw the decision, the judiciary as an institution of lawyers and the Brazilian doctrine . The NCPC has an important role in this process, by not only positivate the binding precedents, as well as to determine important steps towards the constitutionalization process, the judiciary and the decision in a country that has not habituated to democracy. In Brazil historically dominated by positivism to Brazilian bad culture. The great challenge of constitutionalization is not to allow the democratizing innovations become one constitutionalism to the Brazilian bad culture. This is the pursuit of the 1988 Constitution, on that way, the formalist parameter and formal equality gradually lose space for constitutionalism and material equality. Simultaneously, the power brokers are replaced by public agents, whom legitimize their choices by rational reasoning as regards the existing order. Constitutionalize implies democratize. While admitting that the legal rules are not univocal and that the intervenient social Constitution (which should be alive in concrete cases) can not predict all cases in which it is acting, so it must be assumed that the judge will have the task of creating the right in this case. However, the law creating job should be performed based on logical and rational criteria that meet the consistency, integrity and predictability and at the same time keep its eyes on the examinated case. The right created should be able to convince rationally about their legitimacy on the constitutional framework. The case law is formed by the grounds on which it proves the legitimacy of decisions that had created. Both the creation and the application can not lose sight of the commitment to the arguments, the justice for the parties and the rational logic, coherent, fair and predictable with the constitutional order. Then the binding precedents are the result of rational reasoning, logical, coherent, full with the pre-existing law and that proves its legitimacy in the democratic constitutional order.